Effect of pore structure on CO2 gasification reactivity of biomass chars under high-temperature pyrolysis. Issue 3 (June 2020) - Tong, Wei; Liu, Qingcai; Yang, Chen; Cai, Zelong; Wu, Hongli; Ren, Shan
Abstract: The CO2 gasification reactivity of pine sawdust chars (PS char) obtained from the different high-temperature pyrolysis is studied based on non-isothermal thermogravimetric method. Results show that the order of gasification reactivity is PS char-1073 > PS char-1273 > PS char-1473. Under the effect of high-temperature pyrolysis, the surface structure of biomass char is gradually destroyed and the pore structure parameters of specific surface area, total pore volume and average pore diameter increase. By means of the N2 adsorption-desorption isotherms, it is seen that biomass char has more micro- and mesoporous at higher pyrolysis temperature. Besides, the PS char-1073 mostly has rich closed cylinder pores and parallel plate pores, and the PS char-1273 and PS char-1473 have plentiful open cylinder pores and parallel plate pores. An increase of pyrolysis temperature contributes to the development of porosity and improves diffusion path, which promotes the gasification reactivity. But, its effect on the decline of active site hinders the gasification reactivity. What's more, the kinetic model of distributed activation energy model (DAEM) is applied to calculate activation energy and pre-exponential factor with the integral and differential methods. The calculation results of integral method is more accurate and precise because the differential method is more sensitive than integral method for experimental noise. There is a compensation effect in the CO2 gasification process. Highlights: Gasification of biomass chars under different high-temperature pyrolysis are studied. Biomass char has more micro- and mesoporous at higher pyrolysis temperature. An increase of pyrolysis temperature contributes to the development of porosity. Kinetic parameters of integral method is more accurate than differential method.